Kualitas Pelayanan dan Fasilitas Mempengaruhi Kepuasan Konsumen di Bandar Udara Notohadi Negoro Jember - Arif Fakhrudin (Jurnal Manajemen dan Keuangan, 2021)
Transportation is a means that acts as a support, impetus and driving force. So thatpeople are more selective in choosing something, because people want servicesand facilities that exceed consumer expectations. This study aims to determine theeffect of service quality and facilities on customer satisfaction at Notohadi NegoroAirport, Jember. This study use two independent variables, namely the qualityservice and facility with a dependent costumer satisfaction. After a literaturereview and a hypothesis, the data for this study was collected through questionnaires with a total of 100 respondens who used the services of NotohadiNegoro Jember Airport as a research sample. The sampling technique used waspurposive sampling. The methods of data analysis used quantitative analysis,validity test, reliablity test, the multiple regression analysis, t test, f test, and test ofdetermining factor.The result of this study indicate that they are valid and reliable.In the hypothesis test, quality service and facility have a significant positive effecton customer satisfaction. The result of the test of the determining coefficient in thisstudy obtained a determining value of 0,168 which means that the amplitude of theinfluence of the variables quality service and facility on the satisfaction variable is16,8%.